Histological Development of Male Reproductive Organs in Microminipigs - Kangawa, Akihisa; Otake, Masayoshi; Enya, Satoko; Yoshida, Toshinori; Shibata, Masatoshi (Toxicologic pathology, 2016)
Microminipigs are becoming increasingly attractive alternatives for various experimental applications, such as general toxicology studies, owing to their manageable size. However, there are limited studies on the male reproductive organs of microminipigs, particularly on the histological aspects of sexual maturity. To clarify the development of male reproductive organs, 35 male microminipigs, aged 0 to 12 months, were used in this study. Histological and histomorphological evaluation was performed based on spermatogenic development, measurement of tubular structure in testes and epididymides, and histological progress of accessory glands. In addition, spontaneous testicular changes were quantitatively assessed. Histologically, male microminipigs sexually matured around 4.5 months of age, when spermatogenesis in testes and structural development in genital organs were completed. Spontaneous testicular changes occurred in all the animals investigated. Multinucleated giant cell was most commonly observed, followed by hypospermatogenesis and tubular atrophy/hypoplasia. However, the number of affected tubules was less than 1% in testes after 4.5 months of age, suggesting that the influence of these changes on evaluation of toxicity studies may be minimal. It is preferable to use sexually mature animals in toxicology studies; therefore, the information obtained by the present study will be helpful for future toxicity evaluations in microminipigs.